Pengaruh Brand Awareness terhadap Consumer Decision Making The Influence of Brand Awareness to Consumer Decision Making - Ameliawaty, Rianty; Halilah, Ii (Jurnal Riset Bisnis dan Investasi, 2017)
This study to find out how brand awareness in CFC Bandung, how consumer purchasing decisions in CFC Bandung, and how the influence of brand awareness of purchasing decisions in CFC Bandung. This research is done by using quantitative method with descriptive data analysis. The number of samples in this study was 117 consumers who ever made a purchase in CFC Bandung. Test this instrument, reliability test, hypothesis test, simple regression. The results show that brand awareness has influence with  49% by having a significant positive relationship is very strong. The regression equation that can be obtained in this research is Y = 2.494 + 0.370X which shows Constant of 2,494 can be interpreted if brand awareness equal to zero (X = 0) or no brand awareness, then consumer purchase decision only equal to 2.494. Brand awareness has a simple linear regression value of 0.370. This means that brand awareness increases one unit, the consumer purchasing decisions will increase by 0.370 units. This study shows that brand awareness has an influence on consumer purchasing decision in CFC Bandung. Penelitian ini untuk mengetahui bagaimana brand awareness di CFC Bandung, bagaimana keputusan pembelian konsumen di CFC Bandung, dan bagaimana pengaruh brand awareness terhadap keputusan pembelian di CFC Bandung. Penelitian ini dilakukan dengan menggunakan metode kuantitatif dengan analisis data deskriptif. Jumlah sampel dalam penelitian ini adalah 117 konsumen yang pernah melakukan pembelian di CFC Bandung. Uji reliabilitas, R2, uji hipotesis, dan regresi sederhana digunakan pada penelitian ini. Hasil penelitian menunjukkan bahwa kesadaran merek memiliki pengaruh dengan R2 49% dan memiliki hubungan positif yang sangat kuat secara signifikan. Persamaan regresi yang dapat diperoleh dalam penelitian ini adalah Y = 2,494 + 0,370X. Kesadaran merek memiliki nilai regresi linier sederhana yaitu 0,370. Penelitian ini menunjukkan bahwa brand awareness berpengaruh terhadap keputusan pembelian konsumen di CFC Bandung.